(untitled) (Journal of Atomic and Molecular Sciences, 2018)
Stereodynamics for Li+DF/TF→LiF+D/T reactions are studied using the quasi-classical trajectory method based on a new potential energy surface constructed by Aguado and Paniaga [J. Chem. Phys. 119 (2003) 10088]. The product angular distributions of P(θ_r) and P(φ_r), which reflect the vector correlation, are calculated and discussed. The average rotational alignment factor 〈P_2(cosθ_r)〉 as function of the collision energy is also presented. Furthermore, four polarization-dependent differential cross sections (PDDCSs), namely, PDDCS_00, PDDCS_20, PDDCS_21- and PDDCS_22+ are calculated as well. By comparing the stereodynamics results of the title reactions, we find that the isotopic effects are relatively obvious.